Teachers’ Accounts of Multi‑Grade Teaching in the Philippines: A Phenomenological Study - Literal, Marydelle Dianne; Sabud, Marilou (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to describe the accounts or experiences of multigrade teachers. Specifically, it focused on describing teachers' perceptions of multi-grade teaching, their experiences in this context, the strategies they employed to address the challenges they encountered, and their insights into these experiences. The Malungon 1 district served as the study's location. The twelve (12) multi-grade teachers of the East Malungon District participated in this study. The information was gathered through in-depth interviews, and a thematic analysis was employed to examine the data. The study's findings revealed that teachers' views on multi-grade teaching primarily centered on multifaceted pedagogy, which involves managing diverse grade levels to meet learners’ needs. Additionally, in terms of the experiences of teachers in multigrade teaching, the central theme that emerged was navigating a learning environment with the multifaceted nature of teaching that is conducive to diverse grade levels. Additionally, in terms of the strategies employed by teachers to address the challenges they have encountered, the central theme was providing the best services to promote meaningful learning experiences for learners in a multigrade classroom. Lastly, in terms of the insights of the multigrade teachers, the central theme was to commit to cultivating a positive and effective multigrade learning environment through patience, passion, and professional development. In this study, the multi-grade teachers have shared meaningful experiences that can be shared with other teachers in the field. With this, the Department of Education may implement initiatives to address the negative experiences of the multigrade teachers.